Renewable energies in Germany's electricity market a biography of the innovation process - Bruns, Elke.; SpringerLink (Online service). (Netherlands Imprint: Springer, 2011)
This cross-sectional, interdisciplinary study traces the history of innovation of renewable energies in Germany. It features five renewable energy sectors of electricity generation: biomass, photovoltaic, wind energy, geothermal energy and hydropower. The study analyzes the development of the respective technologies as well as their contribution to electricity generation. It focuses on driving forces and constraints for renewable energies in the period between 1990 and today. Through tracking the innovations and mapping the actors, the book answers questions such as: Which technological developments, pivotal actors and actor constellations, which political strategies, goals and instruments play a major role in the innovation process? What legal, administrative, economic and social conditions have been and still are most significant? How do the conflicting aims of environmental protection objectives, including the goals to battle climate change, fit into the larger picture of energy production? Which are the variables that most affect the expansion of renewable energy usage, and in what way?
Acknowledgements -- List of Abbreviations -- List of Figures -- List of Tables -- 1. Introduction -- 2. Introduction to the Methodology -- 3. Cross-Sectoral Interventions, Events and Processes -- 4. Innovation Framework For Generating Biogas and Electricity From Biogas -- 5. Innovation Framework for Generating Electricity From Solar Power -- 6. Innovation Framework For Generating Electricity From Geothermal Power -- 7. Innovation Framework For Generating Electricity From Wind Power -- 8. Innovation Framework For Generating Electricity From Hydropower -- 9. Cross-Sectional Comparison -- 10. Insights Into the Drivers of Innovation -- 10.1 Phase-Specific Adjustment of Policies -- Authors Biographies -- Index of Legal Sources.
Electronic reproduction.
Keywords: Electric utilities -- Government policy -- Germany; Renewable energy sources -- Government policy -- Germany; Electronic books